Essential Oil Compositions of Four Mushrooms: Scleroderma verrucosum, Cortinarius infractus, Hypholama capnoides and Hypholama fasciculare from Turkey - YAYLI, NURAN; YILMAZ, NAGIHAN; OCAK, MIRAC; SEVIM, ALI; SESLI, ERTUGRUL; YAYLI, NURETTIN (Asian Journal of Chemistry, 2010)
The chemical composition of the essential oils obtained from four varieties of Mushrooms, ie. Scleroderma verrucosum, Cortinarius infractus, Hypholama capnoides and Hypholama fasciculare were analyzed by GC-MS. 13, 36, 8 and 10 components, respectively were identified in the essential oils and the main components were found to be 3-octanone from S. verrucosum, musk ambrette from C. infractus, 1-octen-3-ol from H. capnoides and H. fasciculare in the ratios of 49.1, 62.3, 21.7 and 18.2 %, respectively. The isolated essential oils of the fruiting bodies of mushrooms were also tested for antimicrobial activity against the bacteria E. coli, K. pneumoniae, P. aeruginosa, E. faecalis, S. aureus, B. cereus and the fungus C. tropicalis, at maximum essential oil concentrations in hexane of 500, 200, 50 and 250 μg/mL, respectively. No biological activity was observed against all the test microorganisms.